Upregulated miR-101 inhibits acute kidney injury–chronic kidney disease transition by regulating epithelial–mesenchymal transition. (December 2020) - Zhao, J-Y; Wang, X-L; Yang, Y-C; Zhang, B; Wu, Y-B
Acute kidney injury (AKI) is an independent risk factor for chronic kidney disease (CKD). However, the role and mechanism of microRNA (miRNA, miR) in AKI-CKD transition are elusive. In this study, a murine model of renal ischemia/reperfusion was established to investigate the repairing effect and mechanism of miR-101a-3p on renal injury. The pathological damage of renal tissue was observed by hematoxylin and eosin and Masson staining. The levels of miR-101, profibrotic cytokines, and epithelial–mesenchymal transition (EMT) markers were analyzed using Western blotting, real-time polymerase chain reaction, and/or immunofluorescence. MiR-101 overexpression caused the downregulation of α-smooth muscle actin, collagen-1, and vimentin, as well as upregulation of E-cadherin, thereby alleviating the degree of renal tissue damage. MiR-101 overexpression mitigated hypoxic HK-2 cell damage. Collagen, type X, alpha 1 and transforming growth factor β receptor 1 levels were downregulated in hypoxic cells transfected with miR-101 mimic. Our study indicates that miR-101 is an anti-EMT miRNA, which provides a novel therapeutic strategy for AKI-CKD transition.